The The Use of Ecoprocedure Text to Develop the English Reading Materials - Suparman, Suparman; Sani, Hasrul (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
This research is the development of reading material for environmental-based learning to read English. This research designed the types of eco-procedure text to develop the English reading. The purpose of this research is the use of eco-procedure text to develop English reading materials. This research uses the method of educational research and development.  The step of this research modifies into three development steps which consist of 1) research and collecting data, (2) planning, and (3) developing a preliminary form of the product. The results of the research are The eco procedure text prototypes that have been developed are how to make sepat banang, how to make serune pade, how to make soko Sumbawa, and how to make minyak Sumbawa. Then, the elements analyzed in each of the eco procedure prototypes text are the text structure and the linguistic elements of each text. The conclusion of this research is eco procedure text very useful for learning to read students because the eco procedure text is contextual.